1976
DOI: 10.1111/j.1365-2362.1976.tb00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Lipoproteins in Chronic Uraemia. A Study of the Influence of Regular Haemodialysis**

Abstract: Plasma lipids and lipoproteins were studied in a group of chronic uraemia patients some of whom were maintained by regular haemodialysis. Compared with healthy individuals, there was a significant increase in plasma triglycerides and in the prebeta-1- and prebeta-2-lipoprotein plasma concentrations. There was no difference between dialyzed and undialyzed patients. Carbohydrate intake was normal, basal plasma insulin and free fatty acid levels were within the normal range. There was no correlation between plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

1976
1976
2001
2001

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 35 publications
2
22
1
Order By: Relevance
“…The present study confirms previously well-known lipid anomalies in ufaemic patients treated or untreated by intermittent haemodialysis, i. e., hypertriglyceridaemia, a decrease of serum HDL-cholesterol and an increase of the so-called cardiovascular risk factors (13,15,16,(18)(19)(20)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In addition, we have demonstrated that lipid anomalies were more marked in uraemic patients with more advanced renal failure than in those with moderate renal insufficiency.…”
Section: Discussionsupporting
confidence: 77%
“…The present study confirms previously well-known lipid anomalies in ufaemic patients treated or untreated by intermittent haemodialysis, i. e., hypertriglyceridaemia, a decrease of serum HDL-cholesterol and an increase of the so-called cardiovascular risk factors (13,15,16,(18)(19)(20)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In addition, we have demonstrated that lipid anomalies were more marked in uraemic patients with more advanced renal failure than in those with moderate renal insufficiency.…”
Section: Discussionsupporting
confidence: 77%
“…Plasma immunoreactive glucagon (IRG)' is elevated in uremia (1)(2)(3)(4)(5)(6)(7), and a significant portion of the glucagon immunoreactivity is present in a fraction with a mol wt of approximately 9,000 (4,6), consistent with descriptions of proglucagon (8)(9)(10)(11)(12)(13)(14). While changes in glucagon secretion do not appear to be responsible for the increments in total IRG (5,15), the pathogenesis of the alterations in the composition of the circulating hormone is not well understood.…”
Section: Introductionmentioning
confidence: 54%
“…Glucagon is such a hormone, and in uremic man and animals the substantial elevations of its circulating levels and alterations in its immunoreactive composition have beeni attributed to the impaired renal degradation rather than the biochemical environment of uremia (2)(3)(4)(5)(6)(7)(8)(9). In fact, the uremic state per se fails to cause hyperglucagonemia or changes in immunoreactive glucagon (IRG)l composition in animals with normal kidneys rendered azotemic by urine auitoinfusion.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, bilateral nephrectomy, uireteral ligation, or renal pediele-clamping lead promptly to hyperglucagoniemia (3,8,9,22,29,30). In patients with renal failture basal glucagon levels are substantially elevated (2)(3)(4)(5)(6)(7)(8) and the NICR of exogenously adiministered hormone is markedly decreased (5). NMost of the above mentioned studies did not take into account the heterogeneity' of circulating IRG and the alterations in its compositioni which occur in renal insufficiency (6,8,9).…”
mentioning
confidence: 99%